The Development of Contextual Approach Teaching Materials to Improve Students’ Higher Order Thinking Skills (HOTS) - Septripiyani, Kesi; Hidayat, Wahyu; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
This research was motivated by the low results of the Higher Order Thinking Skill (HOTS) abilities of elementary school (SD) students. The low ability of students' Higher Order Thinking Skills is caused by the learning process carried out by the teacher not being in accordance with the learning characteristics related to learning models or approaches in solving problems related to everyday life. The aim of this research is to develop mathematics learning teaching materials, namely using student worksheets to improve the Higher Order Thinking Skills (HOTS) of class VII middle school students that are valid, practical and effective. This research is development research using 4D design. Data collection instruments used validation questionnaires, student response questionnaires, teacher response questionnaires and Higher Order Thinking Skill (HOTS) test instruments. Next, the data analysis technique is by finding the average assessment score and then converting it to the categories previously determined by the researcher. The results of the research stated that the students' worksheet learning teaching materials got an average score of 82 in the very valid category, and the practicality test of the students' aspects of Higher Order Thinking Skills got a score of 81.00 in the practical category. Then, testing the effectiveness of the Higher Order Thinking Skill, there was an increase of 13%, initially getting a score of 69.00 in the initial ability and increasing to 82.00 in the final score.